Affecting factors influencing the deterioration of students discipline in secondary school in Johore - Yahaya, Azizi; Ramli, Jamaluddin; Karrupaya, Shoba (2008)
Discipline problem among secondary scholl students really obvious and always emerged in the local newspapers and this situation dissappointing all the parents and society generally. Star newspaper reported that 28 case discipline problem from January to July 2000. (Sunday Star, July 9, 2000). Berita Harian, 4 November 1998, reported that an average five percent out of 2,500 students of Sekolah Menengah Ibrahim Fikri, seberang Takir have had playing truance. This meant that 250 of the students were found that they commited the problem everyday. The fact is the problem among secondary school students is getting serious and all party should pay more attention due to that the students were our nation unworthy assets.